Lactation failure in crossbred Sahiwal Friesian cattle - Murugaiyah, M.; Ramakrishnan, P.; Sheikh Omar, A.R.; Knight, C.H.; Wilde, C.J. (2001)
Milk producers in Malaysia make extensive use of crossbred Sahiwal Friesian dairy cattle. These animals have, however, been found susceptible to lactation failure. A survey of cows in an experimental herd of F1 Sahiwal Friesian animals indicated that, in 30% of animals, milk yield decreased to negligible levels within the first 8 weeks post partum. Lactation failure was associated with a progressive increase in the amount of residual milk left in the udder after normal milking. By week 3 of lactation, residual milk volume was significantly greater than that in animals that, based on previous lactation history, were not susceptible to lactation failure, and accounted for up to 30% of milk available at the morning milking. The cellular consequences of residual milk accumulation were evident in the activities of acetyl-CoA carboxylase, fatty acid synthetase and galactosyltransferase, key enzyme markers of cellular differentiation, which decreased in glands undergoing lactation failure and were lower than values measured in tissue of control cows. Mammary cell number, estimated by tissue DNA content, was also reduced in animals undergoing lactation failure. These indices of mammary development indicate that lactation failure is the result of premature involution in susceptible animals. Premature involution is a predictable consequence of progressive milk stasis in failing lactation, and attributable to an increase in autocrine feedback by inhibitory milk constituents. The progressive increase in residual milk is, on the other hand, unlikely to be attributable to impaired mammary development. Measurements of milk storage during milk accumulation showed no differences between control and lactation failure cows in the distribution of milk between alveolar and cisternal storage compartments. We conclude that lactation failure in Sahiwal Friesian cows is due to a failure of milk removal, and probably the result of an impaired milk ejection reflex rather than to the glands' milk storage characteristics.